The Allocative Efficiency of the Dutch Gas-Balancing Market. Issue 1 (March 2013) - van Dinther, Arthur; Mulder, Machiel
The recently introduced market-based gas-balancing regime in the Netherlands is meant to improve the efficiency of gas balancing in order to enhance the development of the Dutch wholesale market for gas. This paper shows that the efficiency of the new balancing regime could be improved further by making the market simpler with less restrictive rules. By removing the reserve market, the incentive component as well as the obligation on all players to offer assistance gas, the balancing regime would still enable the TSO to realise network stability but with less allocative inefficiencies.